A preparation method and application of supercapacitor electrode material

The nitrogen-doped porous carbon aerogel with interwoven network structure was prepared by nanocellulose and lignin sulfonate, and hydrothermal reaction and oxalic acid etching were combined with MnO2 to solve the problems of large volume changes and high manufacturing costs during the charge and discharge cycle, and the electrode material with high specific capacitance and good cycle stability was achieved.

CN119742188APending Publication Date: 2025-04-01JIANGSU SUNPOWER +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411786604.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing supercapacitor electrode materials have large volume changes during the charge and discharge cycle, resulting in poor cycle stability and high manufacturing cost of carbon materials derived from fossil raw materials, which limits their application.

Method used

A dual-network aerogel is prepared by using nanocellulose and lignin sulfonate. An interwoven network structure is formed by physical and chemical cross-linking, and nitrogen doping is introduced during the carbonization process to form a nitrogen-doped porous carbon aerogel. Hydrothermal reaction and oxalic acid etching are combined with MnO2 to form an electrode material with high specific capacitance and good cycle stability.

Benefits of technology

It improves the structural stability and electrochemical properties of the electrode material, alleviates the volume changes of MnO2 during charging and discharging, enhances the mechanical stability and electrochemical properties of the material, and simplifies the preparation process without the use of additional binders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742188A_ABST
    Figure CN119742188A_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a supercapacitor electrode material. Iron ions and ethylenediamine are used as crosslinking agents, and a physical and chemical double crosslinking method is adopted to construct a semi-interpenetrating double network hydrogel structure using carboxylated nanocellulose (TOCNFs) and sodium lignin sulfonate (SL). The prepared double network hydrogel is then freeze-dried and carbonized to prepare a nitrogen-doped porous carbon aerogel, and then a hydrothermal reaction is used to synthesize manganese dioxide (MnO2) on the surface of the carbon aerogel. Finally, the prepared material is etched by the reaction of oxalic acid and MnO2. The present invention is simple to operate, low in cost, and the raw materials used are green and environmentally friendly. The electrode material prepared by this method has good structural stability and excellent electrochemical properties, and can be used in high-performance all-solid-state supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of supercapacitors, and in particular relates to a method for preparing a supercapacitor electrode material. Background Art

[0002] In recent years, driven by the growing demand for portable and wearable electronic devices, the market demand and application prospects of supercapacitors have continued to expand. Supercapacitors are electrochemical energy storage devices that rely on polarized electrolytes to store energy. Their high power density, fast charge and discharge speed, and long cycle life make them not only dominant in the field of small electronic devices such as smart water meters and driving recorders, but also have great development potential in large electronic devices such as car starting, wind power generation, and medical X-ray machines. Therefore, how to design high-performance supercapacitors has always been a research hotspot for new energy companies and even the entire energy storage field.

[0003] Although supercapacitors are mainly composed of electrode materials, diaphragms, electrolytes and current collectors, their electrochemical performance depends largely on the electrode materials. The electrode materials currently used are mainly porous materials, such as hydrogels, aerogels, paper-based and paper-like materials, and carbon materials. Compared with the first three materials, carbon materials have high conductivity, adjustable pore structures, and contain a large number of micro- and mesoporous structures, which can meet the rapid diffusion of electrolyte ions. In addition, after being doped with heteroatoms, carbon materials will also have outstanding pseudocapacitive behavior, so carbon materials have always been considered as the preferred materials for supercapacitor electrodes. Even so, carbon materials such as graphene and carbon nanotubes derived from fossil raw materials have become obstacles to their application in the field of supercapacitors due to their high manufacturing costs. Biomass resources are widely present in nature and are renewable resources. They are mainly composed of C, H, and O elements. High-performance carbon materials can be synthesized by pyrolyzing biomass and performing chemical or physical modification. Therefore, using biomass resources to synthesize carbon materials and apply them to supercapacitors is considered to be one of the most promising methods.

[0004] Cellulose is a natural linear high molecular polymer that exists in large quantities in nature. It is composed of glucose linked by 1,4-β glycosidic bonds. Nanocellulose separated from cellulose raw materials by physical and chemical methods has a high elastic modulus and good mechanical properties, and can be used as an elastic substrate for composite materials; and its surface contains a large number of hydrophilic hydroxyl functional groups, which can be chemically modified or composited with other nanomaterials to prepare multifunctional nanocomposites; in addition, carbon materials derived from nanocellulose have rich pore structures, high specific surface areas, and outstanding mechanical stability, and can be used as high-performance flexible electrode materials. Lignin is a by-product of the pulping process in the papermaking industry. It is a complex organic polymer, and its distribution in nature is second only to cellulose and chitin. Lignin and its derivatives contain a variety of active groups. After modification, they can be used to prepare electrode materials with special functions. In addition, lignin has a high carbon content, which can increase the yield of carbon materials when used as a precursor of carbon materials. The double network aerogel prepared from nanocellulose and lignin sulfonate has good mechanical stability, rich pore structure, large specific surface area, can expose more active sites, and can improve the electrochemical and mechanical properties of the material when used as a carbon material precursor. If nanocellulose, lignin and its derivatives are used as raw materials to produce supercapacitor electrode materials, it will be of great benefit to the development of high-performance supercapacitor electrode materials.

[0005] Transition metal oxides have high specific capacitance and low cost. They can be used to modify biomass-derived porous carbon aerogels to increase their specific capacitance exponentially, becoming a modification direction for biomass-derived carbon materials. As a transition metal oxide, manganese dioxide (MnO2) has a high theoretical specific capacitance (1100 F / g) despite its poor conductivity, so its application in the field of energy storage has attracted much attention. However, the volume change of MnO2 is large during the charge and discharge cycle, which can easily lead to poor cycle stability of electrode materials. Combining MnO2 with nanocellulose-derived carbon aerogels can effectively alleviate this defect and improve the electrochemical performance of the material. On the one hand, nanocellulose and lignin sulfonate-derived carbon aerogels can be used as flexible substrates to improve the mechanical properties of composite materials, alleviate the volume change of MnO2 during charge and discharge, and improve cycle stability; on the other hand, the porous carbon network structure can provide a template for the growth of MnO2, prevent the active sites from being covered due to its irreversible aggregation, and improve the electrochemical performance of the material. In addition, nitrogen-doped nanocellulose carbon aerogel has good hydrophilicity, which facilitates the contact between electrode materials and electrolyte ions, thus showing good application prospects in the field of supercapacitors. Summary of the invention

[0006] The present invention aims to provide a method for preparing a supercapacitor electrode material. To achieve the above object, the present invention adopts the following technical solution: A method for preparing a supercapacitor electrode material, the preparation steps are as follows: Dispersing carboxylated nanocellulose TOCNFs in a solvent to obtain a uniformly mixed nanocellulose suspension; Dissolve sodium lignin sulfonate SL into the suspension prepared in 1.1 to obtain a mixed suspension; 1.3. Add the physical crosslinking agent and the chemical crosslinking agent dropwise to the suspension prepared in 1.2 at a mass ratio of 1:1, stir until a hydrogel is formed, then wash with a reagent until neutral, and finally freeze-dry to obtain an aerogel material; 1.4, moving the aerogel obtained in 1.3 into a tubular furnace for heat treatment to obtain a nitrogen-doped porous carbon aerogel material; 1.5. The nitrogen-doped porous carbon aerogel material prepared in 1.4 is subjected to hydrothermal reaction in the reagent for 12 to 24 hours, and then washed and set aside; 1.6. Etch the composite carbon aerogel prepared in 1.5 in the reagent for 5-40 mins, then wash and vacuum dry for 24-48 hours to obtain the electrode material.

[0007] Furthermore, the solvent in step 1.1 is deionized water.

[0008] Furthermore, the physical crosslinking agent described in step 1.2 is a 10% ferric chloride solution, the chemical crosslinking agent is a 10% ethylenediamine solution, the mass ratio of the physical crosslinking agent to the chemical crosslinking agent is 1:1, and the total mass accounts for 5-15% of the nanocellulose suspension. Furthermore, the reagent described in step 1.3 is deionized water, and the deionized water washing is performed by immersion, the immersion times are 3 times, and the single immersion time is 0.5-3h; the freeze-drying time is 48h.

[0009] Furthermore, in step 1.4, the heat treatment carbonization temperature is 800°C, the heating rate is 5°C / min, the carbonization time is 2-8h, and it needs to be carried out in a nitrogen atmosphere.

[0010] Furthermore, the reagent described in step 1.5 is potassium permanganate solution (KMnO4), the concentration of the potassium permanganate solution is 0.1 mol / L, the hydrothermal reaction temperature is 180~240℃, the time is 12~24 h, and the hydrothermal reaction mechanism is: C+2KMnO4=K2MnO4+MnO2+CO2↑.

[0011] Furthermore, the reagent described in step 1.6 is oxalic acid solution (H2C2O4), the concentration of the oxalic acid solution is 0.15 mol / L, the oxalic acid etching time is 5~60 mins, and the etching mechanism is: MnO2+2H2C2O4=MnC2O4+CO2↑+H2O.

[0012] An electrode material prepared by a preparation method, characterized in that the electrode material is a nitrogen-doped three-dimensional porous network structure composite material.

[0013] An application of a supercapacitor electrode material, characterized in that the high-capacity porous electrode can be directly applied to an all-solid-state supercapacitor without the need for other binders.

[0014] An application of a supercapacitor electrode material, characterized in that the application comprises the following steps: 2.1. The prepared nitrogen-doped three-dimensional porous network structure composite material is pressed into a film by a hydraulic press, and then bonded to a copper foil with conductive silver to serve as a supercapacitor electrode; 2.2. Add a diaphragm and a solid electrolyte, and package it to prepare an all-solid-state supercapacitor.

[0015] An application of a supercapacitor electrode material, characterized in that the application comprises the following steps: 3.1. Immerse the supercapacitor electrode prepared in 2.1 into the electrolyte material and air-dry; 3.2. Stack the prepared electrodes and diaphragms, and package them to make an all-solid-state super battery.

[0016] An application of a supercapacitor electrode material, characterized in that the application comprises the following steps: mixing and grinding the prepared nitrogen-doped three-dimensional porous network structure composite material with PVDF, NMP, and conductive carbon black into a uniform slurry, then coating it on a copper foil, and after ventilation drying, cutting it into a target shape and assembling it into an all-solid-state supercapacitor.

[0017] The beneficial effect of the present invention is that TOCNFs and SL form an interwoven network structure after physical and chemical double crosslinking (see the attached crosslinking mechanism). Figure 1 , which improves the structural stability of the carbon aerogel precursor and prevents the collapse of the pore structure during the carbonization process; ethylenediamine not only serves as a cross-linking agent for the preparation of the precursor, but also serves as a nitrogen source during the carbonization process to form nitrogen-doped porous carbon aerogel; the prepared nitrogen-doped carbon aerogel has a rich porous network structure and a high specific surface area, which can expose more active sites, providing a template for the growth of MnO2 while preventing the active sites from being covered after its aggregation; after oxalic acid etching, MnO2 partially decomposes and releases CO2 gas to form a new pore structure, exposing more active sites and improving the electrochemical properties of the material; in addition, the prepared carbon aerogel film can be directly used as a supercapacitor electrode material without the need for a binder, which greatly simplifies the preparation steps. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1: Example 1: Preparation mechanism diagram of nitrogen-doped TOCNFs / SL@MnO2 composite carbon aerogel precursor; Figure 2 :Porous carbon aerogel assembled into a solid-state supercapacitor structure diagram; Figure 3 : Example 1 N2 adsorption-desorption curve and pore size distribution curve of nitrogen-doped TOCNFs / SL@MnO2 composite carbon aerogel (embedded part); Figure 4 : CV curve of nitrogen-doped TOCNFs / SL@MnO2 composite carbon aerogel in Example 1; Figure 5 : Nyquist plot of nitrogen-doped TOCNFs / SL@MnO2 composite carbon aerogel in Example 1; Figure 6 : Example 2 Cycle curve of all-solid-state supercapacitor assembled with nitrogen-doped TOCNFs / SL@MnO2 composite carbon aerogel. DETAILED DESCRIPTION

[0019] In order to explain the technical content clearly, it is described below in conjunction with specific embodiments.

[0020] Example 1. Preparation of carbon aerogel material Take 0.5g TOCNFs and disperse them in 99.5mL deionized water. Stir magnetically for 3 hours to make TOCNFs completely dispersed, without agglomeration and form a uniform suspension. Then disperse 0.5g SL in the TOCNFs suspension until SL is completely dissolved. Then, add 10g of the prepared ferric chloride solution and ethylenediamine solution to the mixed suspension in turn, and stir magnetically until a hydrogel is formed. The mass ratio of ferric chloride to ethylenediamine is 1:1. Then soak the prepared hydrogel in deionized water for 6~9 hours until the unreacted reagent is completely removed, and change the water 3~5 times during this period. Then freeze the prepared hydrogel in a -20℃ environment for 12 hours, place the frozen hydrogel sample in a freeze dryer for 48 hours, and freeze-dry to form a TOCNFs / SL composite aerogel. Then, the prepared TOCNFs / SL composite aerogel was used as a carbonization precursor and placed in a tubular furnace for high-temperature carbonization to prepare nitrogen-doped TOCNFs / SL composite carbon aerogel. The carbonization temperature was 800°C and it had to be carried out in a nitrogen atmosphere. The heating rate was 5°C / min and the carbonization time was 4 h. The prepared nitrogen-doped TOCNFs / SL composite carbon aerogel was used as the substrate, and MnO2 was synthesized on its surface by hydrothermal reaction. A 0.1 mol / L potassium permanganate solution was placed in a hydrothermal reactor, and then the prepared carbon aerogel was placed in a hydrothermal reactor for reaction for 24 h. The hydrothermal reaction temperature was 200°C. The prepared composite material was ultrasonically cleaned in deionized water for 3 to 4 times to remove the unreacted reagent potassium permanganate, and then the prepared composite material was etched in a 0.15 mol / L oxalic acid solution for 10 mins, and then rinsed with deionized water until neutral and dried in a vacuum drying oven for 48 h. Figure 3 As shown in Figure 2, the specific surface area of ​​the prepared nitrogen-doped carbon TOCNFs / SL@MnO2 composite carbon aerogel is 524 m 2 / g, and contains a large number of mesoporous structures (2~50 nm), which will provide an effective way for the transmission of electrolyte ions. The prepared composite carbon aerogel was pressed into a film by a hydraulic press, and then cut into a target shape. The cyclic voltammetry curve was measured by a three-electrode system, and the cyclic voltammetry curve was a rectangular curve with redox peaks (such as Figure 4 ) indicates that the material has both electric double layer behavior and pseudocapacitive behavior. As a result, the internal resistance of the prepared carbon aerogel electrode material is 0.5 Ω (e.g. Figure 5 ), and has a specific capacitance of 875 F / g.

[0021] Example 2: Application of self-supporting porous carbon aerogel materials in all-solid-state supercapacitors The prepared carbon aerogel film is directly used as an electrode material without the need for additional binder. The carbon aerogel film is glued to copper foil with conductive silver glue and used as the electrode of the supercapacitor. Then, electrolyte and diaphragm are added to assemble a solid-state supercapacitor. The structure of the supercapacitor is shown in the attached figure. Figure 2 As shown, 1 is a current collector, 2 is a solid electrolyte, 3 is a carbon aerogel membrane electrode, the solid electrolyte 2 is provided with upper and lower carbon aerogel membrane electrodes 3 respectively, and the outer layers of the upper and lower carbon aerogel membrane electrodes 3 are provided with a current collector 1, wherein the solid electrolyte is prepared by adding 6g KOH and 6g PVA to 60ml water, stirring and swelling at 40 degrees for 1.5h, then heating to 85 degrees, stirring at a constant temperature of 85 degrees until the solution is clear, and then cooling to obtain the obtained supercapacitor. After 8000 cycles, the capacitance retention rate of the prepared supercapacitor is 95.91% (as shown in FIG. Figure 6 This result indicates that when MnO2 is loaded on the porous carbon aerogel, the porous carbon aerogel can act as a flexible substrate to alleviate the volume change of MnO2 during the charge and discharge process. As a result, the prepared composite aerogel has excellent cycle stability.

[0022] Example 3: Application of porous carbon aerogel materials in all-solid-state supercapacitors The prepared carbon aerogel was ground into a uniform slurry with PVDF, NMP, and conductive carbon black in proportion, and then coated on a copper foil, placed in a fume hood to dry, cut into the target shape, and then Figure 2 Assembled into a fully solid-state supercapacitor.

Claims

1. A method for preparing a supercapacitor electrode material, the preparation steps of which are as follows: Dispersing carboxylated nanocellulose TOCNFs in a solvent to obtain a uniformly mixed nanocellulose suspension; Dissolve sodium lignin sulfonate SL into the suspension prepared in 1.1 to obtain a mixed suspension; 1.

3. Add the physical crosslinking agent and the chemical crosslinking agent dropwise to the suspension prepared in 1.2 at a mass ratio of 1:1, stir until a hydrogel is formed, then wash with a reagent until neutral, and finally freeze-dry to obtain an aerogel material; 1.4, moving the aerogel obtained in 1.3 into a tubular furnace for heat treatment to obtain a nitrogen-doped porous carbon aerogel material; 1.

5. The nitrogen-doped porous carbon aerogel material prepared in 1.4 is subjected to hydrothermal reaction in the reagent for 12 to 24 hours, and then washed and set aside; 1.

6. Etch the composite carbon aerogel prepared in 1.5 in the reagent for 5-40 mins, then wash and vacuum dry for 24-48 hours to obtain the electrode material.

2. The method for preparing a supercapacitor electrode material according to claim 1, characterized in that: The solvent in step 1.1 is deionized water.

3. The method for preparing a supercapacitor electrode material according to claim 1, characterized in that: The physical crosslinking agent described in step 1.2 is a 10% ferric chloride solution, the chemical crosslinking agent is a 10% ethylenediamine solution, the mass ratio of the physical crosslinking agent to the chemical crosslinking agent is 1:1, and the total mass accounts for 5-15% of the nanocellulose suspension.

4. The method for preparing a supercapacitor electrode material according to claim 1, characterized in that: The reagent described in step 1.3 is deionized water, and the deionized water washing is performed by immersion, the immersion times are 3 times, and the single immersion time is 0.5-3h; the freeze-drying time is 48h.

5. The method for preparing a supercapacitor electrode material according to claim 1, characterized in that: Step 1.4: The heat treatment carbonization temperature is 800°C, the heating rate is 5°C / min, the carbonization time is 2-8 h, and it needs to be carried out in a nitrogen atmosphere.

6. The method for preparing a supercapacitor electrode material according to claim 1, characterized in that: The reagent described in step 1.5 is potassium permanganate solution (KMnO4), the concentration of potassium permanganate solution is 0.1 mol / L, the hydrothermal reaction temperature is 180~240℃, the time is 12~24 h, and the hydrothermal reaction mechanism is: C+2KMnO4=K2MnO4+MnO2+CO2↑.

7. The method for preparing a supercapacitor electrode material according to claim 1, characterized in that: The reagent described in step 1.6 is oxalic acid solution (H2C2O4), the concentration of the oxalic acid solution is 0.15 mol / L, the oxalic acid etching time is 5~60 mins, and the etching mechanism is: MnO2+2H2C2O4=MnC2O4+CO2↑+H2O.

8. An electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The electrode material is a nitrogen-doped three-dimensional porous network structure composite material.

9. A use of a supercapacitor electrode material as claimed in claim 8, characterized in that: The high-capacity porous electrode can be directly applied to an all-solid-state supercapacitor without the need for other binders.

10. A use of a supercapacitor electrode material as claimed in claim 9, characterized in that: The application The following steps are involved: 2.

1. The prepared nitrogen-doped three-dimensional porous network structure composite material is pressed into a film by a hydraulic press, and then bonded to a copper foil with conductive silver to serve as a supercapacitor electrode; 2.

2. Add a diaphragm and a solid electrolyte, and package it to prepare an all-solid-state supercapacitor.

11. A use of a supercapacitor electrode material as claimed in claim 9, characterized in that: The application The following steps are involved: 3.

1. Immerse the supercapacitor electrode prepared in 2.1 into the electrolyte material and air-dry; 3.

2. Stack the prepared electrodes and diaphragms, and package them to make an all-solid-state super battery.

12. A use of a supercapacitor electrode material as claimed in claim 9, characterized in that: The application includes the following steps: mixing and grinding the prepared nitrogen-doped three-dimensional porous network structure composite material with PVDF, NMP, and conductive carbon black into a uniform slurry, then coating it on a copper foil, and after ventilation drying, cutting it into a target shape and assembling it into an all-solid-state supercapacitor.

Citation Information

Cited By

  • Preparation method and application of flexible supercapacitor electrode material

    CN121439540A